Evaluation of Ultra-High Molecular Weight Polyethylene (UHMWPE) Implants in Orbital Fracture Reconstruction: A Multicenter Cohort Study - Afxentiou, Konstantinos; Preidl, Raimund; Kesting, Marco Rainer; Aksu, Adem; von Bomhard, Achim; Pippich, Katharina; Wilhelm, Stefanie; Lutz, Rainer (Journal of Maxillofacial and Oral Surgery, 2025)
Purpose: Orbital wall reconstruction remains a challenge in reconstructive CMF surgery due to the delicate anatomical structures and their potential functional impairment due to inefficient treatment. The use of biomaterials in reconstructive surgery has revolutionised the therapy in this area. Ultra-high molecular weight polyethylene (UHMWPE) has shown promising results due to its biocompatibility, mechanical properties, and versatility. This paper presents the first clinical study of the use of UHMWPE in orbital fracture reconstruction. Methods: In a multicentre prospective study consisting of 50 patients undergoing orbital floor reconstruction, UHMWPE implants were used to reconstruct the orbital volume after fracture. 46 Patients underwent preoperative and postoperative 3D radiography and orbital volume segmentation. Results: A significant postoperative volume reduction of the affected orbits was observed in the entire cohort (p < 0.001) with a significant alignment to the healthy contralateral orbits. There were no implant-related complications. Conclusion: Orbital wall reconstruction with UHMWPE (marPOR) implants is a reliable method to restore adequate orbital volume for functional and aesthetic recovery in trauma patients.
CRIS-Team Scopus Importer:2025-07-18
Keywords: marPOR; Orbital floor fractures; Orbital volumes; Ultra/high molecular weight polyethylene